Low serum total testosterone level as a predictor of upgrading in low-risk prostate cancer patients after radical prostatectomy: A systematic review and meta-analysis - Shu Gan; Jian Liu; Zhiqiang Chen; Songtao Xiang; Chiming Gu; Siyi Li; Shusheng Wang (Investigative and Clinical Urology, 2022)
Purpose: To investigated the association between serum total testosterone and Gleason score upgrading of low-risk prostate cancer after radical prostatectomy (RP). Materials and Methods: Medline, Web of Science, Embase, and Cochrane Library databases were searched to identify eligible studies published before October 2021. Multivariate adjusted odds ratios (ORs) and associated 95% confidence intervals (CIs) were calculated using random or fixed effects models. Results: Five studies comprising 1,203 low-risk prostate cancer patients were included. The results showed that low serum total testosterone (<300 ng/dL) is associated with a high rate of Gleason score upgrading after RP (OR, 2.3; 95% CI, 1.38–3.83; p<0.001; I2, 92.2%). Notably, sensitivity and meta-regression analyses further strengthen the reliability of our results. Conclusions: Our results support the idea that low serum total testosterone is associated with a high rate of Gleason score upgrading in prostate cancer patients after RP. It is beneficial for urologist to ensure close monitoring of prostate-specific antigen levels and imaging examination when choosing non-RP treatment for low-risk prostate cancer patients.